Greenhouse Gas Emissions (GHG) Estimation in the Livestock Sector in Bangka Belitung Province using the IPCC Tier-2 Method - Puspito, Sigit; Wardi; Haryanto, Bambang; Suharyanto; Andri Yano, Aan; Firmansyah, Angga Maulana; Hayati, Rini Nur; Ismiarti; Pratiwi, Nugraheni Nur (Faculty of Animal Science, Jenderal Soedirman University in associate with the Animal Scientist Society of Indonesia (ISPI) and the Indonesian Association of Nutrition and Feed Science (AINI), 2024)
Greenhouse gas (GHG) emissions were a major causal factor of global warming that further impacts climate change. This study aimed to inventory the sources of greenhouse gas emissions from the livestock sector in Bangka Belitung. The GHG emissions in the livestock sector was calculated using the Tier-2 method based on guidance from IPCC 2006. Secondary data were collected from multiple sources, including livestock population, enteric CH4 emission factors, and the production and management of local livestock manure. The results of the calculation of GHG emissions in Bangka Belitung from 2018-2022 showed a significant increase from 25.54 to 33.32 Gg CO2 eq, with an accumulation of 139.43 Gg CO2 eq over five years. Beef cattle became the largest contributor to GHG emissions, with enteric fermentation CH4 emissions of 104.34 Gg CO2 eq, accounting for 91.90% of the total CH4 emissions from enteric fermentation sources and 74.84% of the total GHG emissions in Bangka Belitung. The largest contributor to GHG emissions was 78.62% or 109.62 Gg CO2 eq from enteric fermentation sources of ruminants, while N2O emissions from manure management reached 29.10 Gg CO2 eq, and the smallest CH4 emissions were 0.70 Gg CO2 eq, sourced from livestock manure